Hubungan Pemahaman Materi UUD Negara Republik Indonesia Tahun 1945 dengan Civic Disposition (Studi Ex-Post Facto pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan Siswa Kelas VIII SMPN 20 Jakarta) - Putranto, Hazmin Hafid; Ramadhan, Abhi Rachma; Nuriyani, Riska; Putra, Muhammad Lathief Dwi; Adnin, Ismi (Ideas Publishing, 2024)
The problem of civic character, or what is commonly known as civic disposition, is not an open secret and has become a major concern of various nations and countries. So this research was born with the aim of exploring the relationship between understanding the material of the 1945 Constitution of the Republic of Indonesia and civic disposition in class VIII students at SMPN 20 Jakarta. A quantitative method with an ex-post facto approach was used, involving 323 students as a population using random sampling techniques and producing 179 respondents. The research begins with testing the instrument, then its validity and reliability. So it shows understanding of the material with an average of 23.87 (78.77%) and civic disposition 100.80 (77.09%). Statistical analysis confirmed the existence of a positive and significant relationship between the two (rcount > rtable, 0.186 > 0.145, significance 0.01 < 0.05), with a coefficient of determination of 7.7%. The implication is that this research highlights the importance of understanding Constitutional material in forming students' civic disposition, although its contribution is low but significant.